Peran E-Commerce dalam Meningkatkan Akses Pasar bagi Produk UMKM Lokal di Kota Serang - Vera Maria; Sebastian Nicodemus Gunawan; Najla Indira Faradiva; Hilda Agustiani; Dinda Cahya Ramadhan; Fadya Salamah (Journal of Management and Social Sciences, 2024)
The development of MSMEs (Micro, Small, and Medium Enterprises) in Indonesia has been quite rapid, especially with the occurrence of the Covid-19 pandemic worldwide, which has dampened economies globally. Several studies have also found that MSMEs and cooperatives play a crucial role in driving local economic growth by creating new job opportunities, especially in underdeveloped areas. With the presence of MSMEs and support for digitalization through the utilization of e-commerce platforms, this becomes one of the essential strategies for MSME players in Indonesia, particularly in Serang City, to market and promote their products widely. The research method employed is a case study based on previous research on the impact of MSMEs that have adopted e-commerce. The research results indicate that the implementation of e-commerce has a significant positive influence on the growth of MSMEs in Serang City.